Determination of Nutrient Elements in Seven Species of Ganodermataceae - Jin1, Pengcheng; Li2, Tao; Zhao3, Yanli; Li4, Jieqing; Shen2, Tao; Chen1, Xi; Wang3, Yuanzhong; Liu4, Honggao (Asian Journal of Chemistry, 2013)
The nutrient elements (C, Ca, Cr, Cu, Fe, K, Mg, Mn, N, Na, Ni, P, Pb, Sr and Zn) in seven species of Ganodermataceae collected from different locations of Yunnan were established by atomic absorption spectrometry. Ganodermataceae samples contained C (571.31-722.93 μg g-1), Ca (52.14-3044.32 μg g-1), Cr (0.49-12.47 μg g-1), Cu (7.22-48.34 μg g-1), Fe (77.88-2591.02 μg g-1), K (1372.07-6944.67 μg g-1), Mg (291.95-660.48 μg g-1), Mn (12.63-240.45 μg g-1), N (1.25- 3.74 μg g-1), Na (119.41-3205.38 μg g-1), Ni (1.22-5.23 μg g-1), P (160.54-356.54 μg g-1), Pb (0.75-16.9 μg g-1), Sr (0.18-52.27 μg g-1) and Zn (16.95-72.03 μg g-1). The nutrient contents of Ganodermataceae showed a wide variability among different species. The results would be useful for exploitation and quality evaluation of wild Ganodermataceae in Yunnan province of China.